Multicenter experience with digital single-operator cholangioscopy in pregnant patients - Brewer Gutierrez, Olaya I.; Godoy Brewer, Gala; Zulli, Claudio; Tejaswi, Sooraj; Pawa, Rishi; Jamidar, Priya; Robles-Medranda, Carlos; Pawa, Swati; Camilion, Jose V.; Oleas, Roberto; Parsa, Nasim; Runge, Thomas; Miaw, Diana; Ichkhanian, Yervant; Khashab, Mouen A. (Endoscopy International Open, 2021)
Background and study aims The use of fluoroscopy during pregnancy should be minimized given that a clear-cut safe radiation dose in pregnancy is unknown. The role of digital single-operator cholangioscopy (D-SOC) as an alternative to standard enodoscopic retrograde cholangiopancreatography (ERCP) in pregnant patients has not been comprehensively studied. This study assessed 1 Technical success defined as performance of ERCP with D-SOC without the use of fluoroscopy in pregnant patients; 2 safety of D-SOC in pregnancy; and 3 maternal and neonatal outcomes after D-SOC during/after pregnancy. Patients and methods This was an international, multicenter, retrospective study at 6 tertiary centers. Pregnant patients who underwent D-SOC for the treatment of bile duct stones and/or strictures were included. Results A total of 10 patients underwent D-SOC. Indications for ERCP were choledocholithiasis, strictures, previous stent removal, and choledocholithiasis/stent removal. Bile duct cannulation without fluoroscopy was achieved in 10 of 10 patients (100 %). Moreover, 50 % of patients (5/10) completed a fluoroless ERCP with D-SOC. Mean fluoroscopy dose and fluoroscopy time were 3.4 ± 7.2 mGy and 0.5 ± 0.8 min, respectively. One case of mild bleeding and one case of moderate post-ERCP pancreatitis occurred. The mean gestational age at delivery was 36.2 ± 2.6 weeks. Median birth weight was 2.5 kg [IQR: 2.2–2.8]. No birth defects were noted. Conclusion ERCP guided by D-SOC appears to be a feasible and effective alternative to standard ERCP in pregnant patients. It enables avoidance of radiation in half of cases.